Entrepreneurship, Empowerment, and Development : Unraveling Economic Rationales in Sweden’s Feminist Foreign Policy - Bullock, Lukas ; 0000-0002-0677-6833 (Foreign Policy Analysis, 2025)
Between 2014 and 2022 Sweden operated the world’s first feminist foreign policy (FFP), which has drawn strong reactions from academics and activists alike. The overarching aim of this article is to analyze how economic objectives within Sweden’s deployment of FFP were framed and rationalized in policy programming, which has to this point received little scholarly attention. Drawing from empirical data, including government texts, published interviews, and a public-facing embassy exhibit, this article argues that the economic programming within FFP was strongly influenced by market feminism. The supporting evidence thematically covers the strong rhetorical focus in FFP documents on investing in impoverished women as a driver of global economic growth, the promotion of specific policies that focused on uplifting women’s entrepreneurship, and the significant role that public–private partnerships played in the enactment of a number of policy initiatives. The insights of this article highlight how foreign policy programs, gender equality, and neoliberalism are increasingly shaping one another.